# Given the function f(x) = 3(x + 2) - 4, solve for the inverse function when x = 2.

**Solution:**

Given: Function f(x) = 3(x + 2) - 4

Consider f(x) as y

y = 3(x + 2) - 4

Replace x by y

x = 3(y + 2) - 4

It can be written as

x + 4 = 3(y + 2)

Divide both sides by 3

(x + 4)/3 = y + 2

(x + 4)/3 - 2 = y

So f^{-1}(x) = (x + 4)/3 - 2

Let us solve by substituting x as 2

f^{-1}(2) = (2 + 4)/3 - 2

By further calculation

f^{-1}(2) = 6/3 - 2

f^{-1}(2) = 2 - 2

f^{-1}(2) = 0

Therefore, the inverse function when x = 2 is 0.

## Given the function f(x) = 3(x + 2) - 4, solve for the inverse function when x = 2.

**Summary:**

Given the function f(x) = 3(x + 2) - 4, the inverse function when x = 2 is 0.